O controle judicial e o papel das funções essenciais à Justiça para a efetivação das políticas públicas - Murda, Paula Fernanda Vasconcelos Navarro (2012)
The present dissertation is about the judicial control and the role of the Justice s essential activities for the effectiveness of public policies and the role of the other institutions considered essential for the effectiveness of Justice. This work has as starting point an overview on the State functions and the criteria used to distinguish one from each other. Following this, an analysis over the concepts and characteristics surrounding the notion on public policies is carried on, among which special emphasis is given to the State s commisive and ommisive programs, stability, the possibility of judicial control, the teleological element and the conditions regarding the existence of public policies, that are the political decisions, the creation of laws and the execution of technical acts. In the sequence, the judicial control over public policies is analyzed, starting from the analysis of the grounds under which the judicial control is authorized, and over the acts of the other Powers, until the constitutional basis for the control over public policies. The assessment procedural study proposed by Robert Alexy, as well as the analysis of some of the guiding constitutional principles of judicial decisions are carried on. Following this, the author studies the favorable and non-favorable arguments regarding the judicial intervention over public policies and the required compatibility between the arguments, among which the highest effectiveness of constitutional rules, the minimal existentialism, the theory of happiness, the theory of regression blockage, the possible reservation and budget issues. In terms of instruments for the effectiveness of public policies, the constitutional control, the legislative omission and the control over administrative acts are assessed. The comprehension of illegal removal powers for the effectiveness of public policies is carried out pursuant to the analysis of judicial measures of coercion, among which mandatory rulings demanding actions, the sanctioning of daily penalties, federal or state intervention and the liability of the public agents. The alternative methods for conflict s resolution are examined. Finally, an analysis over the role of the other essential judicial activities for the effectiveness of public policies is carried on. The author assesses the activities of the Public Prosecutor Office on the control over the budget implementation, as well as the available tools given for that, among which the public civil lawsuit (class action), the civil investigation, the term of adjustment of conduct and the ministry recommendation. The role of the Public Defense Office is analyzed under the standpoint of the required structuring of the career in all Federative States, as well as under the protection of the interests of careless individuals, not only in Courts, but also through a global legal orientation. On the role of the Public Advocacy, the assessment of the public attorneys behavior in taking care of such procedures, the functional independence and the orientation from the federative body for the collaboration for the effectiveness of public policies is carried on